Enhancing drought tolerance in Indian mustard (Brassica juncea) through microbial inoculants under varying irrigation regimes - KUMAWAT, PRIYANKA; RAM, MANOHAR; JAKHAR, M L; KUMAR, PANKAJ; KUMAWAT, G L; MANJEET; RAJPAUL (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the winter (rabi) seasons of 2020–21, 2021–22 and 2022–23 at College of Agriculture, Sri Karan Narendra Agriculture University, Jobner, Rajasthan to identify the appropriate bacterial strains and irrigation levels to enhance drought tolerance and productivity in Indian mustard [Brassica juncea (L.) Czern.]. The experiment was laid out in a split plot design assigning irrigation treatments (no irrigation, 50% deficit irrigation and normal level of irrigation) in main plots and microbes (MRD-17, MKS-6, Biophos and Biophos+, CRIDAMI-I, CRIDA MI-II and control) in sub plots. Results demonstrated that normal level of irrigation (2 irrigations) yielded superior outcomes in terms of plant height, dry matter accumulation, yield attributes, viz. seed yield (1542 kg/ha), stover yield (3677 kg/ha), relative water content (70.72%), protein content (18.1%), oil content (38.7%), water use efficiency (7.50 kg/ha-mm), net returns (₹52529/ha) and B:C ratio (2.07). This was significantly higher compared to 50% deficit irrigation and no irrigation treatments. Among microbial inoculants, CRIDA MI-II exhibited the highest impact on growth and yield attributes, viz. seed yield (1312 kg/ha), stover yield (3262 kg/ha), protein content (17.2%), water use efficiency (5.88 kg/ha-mm), net returns (₹42294/ha) and B:C ratio (1.72). Notably, it was statistically comparable to the effects of CRIDA MI-I and Biophos and Biophos+ across most parameters. The comprehensive results of this study advocated the strategic implementation of both optimal irrigation practices and microbial inoculants as a sustainable approach to enhance productivity and drought tolerance in Indian mustard, particularly in the arid and semi-arid regions of Rajasthan.